2013
DOI: 10.1371/journal.pone.0071174
|View full text |Cite
|
Sign up to set email alerts
|

Virologic and Immunologic Response to cART by HIV-1 Subtype in the CASCADE Collaboration

Abstract: BackgroundWe aimed to compare rates of virologic response and CD4 changes after combination antiretroviral (cART) initiation in individuals infected with B and specific non-B HIV subtypes.MethodsUsing CASCADE data we analyzed HIV-RNA and CD4 counts for persons infected ≥1996, ≥15 years of age. We used survival and longitudinal modeling to estimate probabilities of virologic response (confirmed HIV-RNA <500 c/ml), and failure (HIV-RNA>500 c/ml at 6 months or ≥1000 c/ml following response) and CD4 increase after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…Legal barriers also exist despite all public health recommendations and scientific evidence supporting universal access to HIV testing and treatment; this is still denied to undocumented migrants in some European countries . Migrants are thought to have poorer adherence secondary to socio‐economic factors . Whereas this has previously been shown for some groups of migrants, our data illustrate that this finding cannot be generalized to all migrant groups.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Legal barriers also exist despite all public health recommendations and scientific evidence supporting universal access to HIV testing and treatment; this is still denied to undocumented migrants in some European countries . Migrants are thought to have poorer adherence secondary to socio‐economic factors . Whereas this has previously been shown for some groups of migrants, our data illustrate that this finding cannot be generalized to all migrant groups.…”
Section: Discussioncontrasting
confidence: 53%
“…Data on administrative/legal status for migrant populations in COHERE are not collected. Viral clade and subtype data were not available for this analysis, but the CASCADE Collaboration in EuroCoord has found no clinically relevant differences in either immunological or virological response to cART by HIV‐1 subtype .…”
Section: Discussionmentioning
confidence: 99%
“…Distinct prevalence of drug resistance mutations (DRMs) and kinetics of DRM emergence were observed among HIV-1 subtypes [ 14 18 ], although other studies indicated that outcomes of antiretroviral therapies (ART) may not be affected by subtypes and differences in virological and immunologic responses to ART might be contributed by ethnicity and/or adherences [ 19 21 ]. Drug resistance mutations (DRMs) are a major cause of antiretroviral therapy failure, and hence surveillance for the emergence of drug resistance among all subtypes and recombinants has been implemented in ART programs.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the ongoing residual viraemia, up to 200 copies/ml, for 6–9 months enhances the risk of virologic failure [Laprise et al, ]. On contrary, there are studies that do not relate residual viraemia with increased risk of virologic failure [Scherrer et al, ; Charpentier et al, ; Touloumi et al, ; Charpentier et al, ]. In this study, no difference in rates of virological failure was observed between the two groups, above and below 50 copies/ml, after 1 year of follow‐up.…”
Section: Discussionmentioning
confidence: 51%